Experimental Methods of Determination of Short- and Long-term Mechanical Strength of Ceramic Insulators - Rejmund, F.; Ranachowski, P. (Engineering Transactions, 1998)
The subject of this paper are the properties of ceramic insulators responsible for transmission of mechanical stresses due to their construction and destination. Taking into account the information about failure of the insulators, the effect of electrical stresses imposed on the insulator structure by the electric field can be neglected. In view of this fact, our considerations concern the parameters characterising short and long-term mechanical strengths and the method of forecasting the minimal time to the mechanical failure.